Lifestyle intervention improves Left atrial strain in type 2 diabetes: results from the DIASTOLIC randomised trial. (14th October 2021) - Alfuhied, A; Gulsin, G S; Brady, E M; Parke, K; Athithan, L; Henson, J; Redman, E; Yates, T; Davies, M J; Marsh, A M; McCann, G P; Singh, A
Abstract: Introduction: Left atrial (LA) strain has been shown to be an independent predictor of cardiovascular events in many conditions and superior to conventional measures of LA function (LA volumes and emptying fraction). The effects of low-energy diet or exercise on cardiovascular function in younger adults with type 2 diabetes (DIASTOLIC) study has previously demonstrated an improvement in left ventricle peak early diastolic strain rate in response to aerobic exercise in patients with type-2 diabetes (T2D). However, the effect of lifestyle intervention on LA function, assessed by cardiac magnetic resonance (CMR) imaging, is unknown. Methods: The DIASTOLIC study was a prospective, randomised, open-label, blind endpoint trial, that randomised 90 obese participants with T2D (aged 18–65 years) to a 12-week intervention of: (i) routine care, (ii) aerobic exercise training, or (iii) low energy (≈810kcal/day) meal replacement plan (MRP). CMR was performed at baseline and week-12. Images were analysed using Medis v3.1. LA strain (LAS) was assessed using Feature Tracking (QStrain v2.0), corresponding to LA reservoir (LAS-r), conduit (LAS-cd), and booster pump (LAS-bp) using 4- and 2-chamber standard steady-state free precession cine images, and average values calculated. LA emptying fraction (LAEF) was calculated using biplane area-length method (QMass v8.1) for total, passive and active EF. Results: 73 participants with T2D completed the trial and had analysable LA images (28 routine care, 22 exercise and 23 MRP). There was no significant change in CMR measured standard LA volumetric function (LAV/LAEF) and echocardiogram measured LV filling pressures (E/e') in any groups. The routine care arm showed no significant change in body mass index (BMI) or LAS (see Table). In the MRP group, there were significant reductions in BMI (4.8 kg/m 2 ), mean systolic blood pressure (SBP) (13mmHg), and a significant increase in LAS-r and LAS-bp (29.9±7.0 to 32.3±7.0, p=0.036 and 14.6±5.3 to 17.2±3.7, p=0.034). The exercise arm showed a small reduction in BMI (0.8kg/m 2 ), with no significant change in BP or LAS. Conclusion: There was significant improvement in LAS post-lifestyle intervention in young adults with T2D, despite no change in volumetric measurements. MRP led to weight loss and improved SBP, with associated improved LA filling and contraction. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Institute for Health Research (NIHR) a career development fellowship.